КРЕДИТ ТАЪЛИМ ТИЗИМИНИ ЖОРИЙ ЭТИШДА ПРОФЕССОР-ЎҚИТУВЧИЛАРНИНГ РОЛИ - Ашурова, Д.Х. (SCIENCE and SOCIETY, 2022)
The main goal of every pedagogue is first of all to show their individuality through their pedagogical skills, to form a culture of independent thinking in classes by means of interactive educational methods, and thereby to increase the activity of students. Organization of training sessions on the basis of the credit-module system significantly increases the role of pedagogues in the educational process.
Keywords: world educational standards; pedagogical skills; pedagogical activity in the modular system of education; the main tasks of teachers; characteristics of the teacher as an evaluator